Effects of creep feeder design and feed accessibility on preweaning pig performance and the proportion of pigs consuming creep feed - R C Sulabo; Michael D Tokach; Joel M DeRouchey; Steven S Dritz; Robert D Goodband; Jim L Nelssen (Kansas Agricultural Experiment Station Research Reports, 2010)
Objective: To determine the effects of creep feeder design and feed accessibility on preweaning performance and the proportion of eaters of creep feed. Materials and methods: A total of 54 sows and their litters were assigned to three treatments: rotary feeder with hopper, rotary feeder without hopper, and pan feeder. A creep diet with 1.0% chromic oxide was offered ad libitum from Day 18 until weaning (Day 21). Fecal samples were collected from piglets with sterile swabs 3 to 12 hours before weaning. Piglets were categorized as "eaters" when either of the two fecal samples was colored green; otherwise, they were categorized as "non-eaters." Pigs were weighed Days 0 (birth), 18, and 21, and litter creep-feed disappearance was determined daily. Results: There were no differences (P>.05) in preweaning gains and weaning weights of pigs and litters using the different types of creep feeder. Litters provided creep feed using the rotary feeder with the hopper had 2.7 times lower total creep-feed disappearance than litters using the rotary feeder without the hopper and the pan feeder (P<.001). However, the rotary feeder with the hopper produced the highest proportion of pigs consuming creep feed within the litter (80%; P<.001). Implications: The proper choice of creep feeder is essential to manage creep feeding and to maximize the number of eaters in the litter. A creep feeder with a hopper may create more eaters with less feed wastage.; Journal of Swine Health and Production; 18; Swine Day, 2010, Kansas State University, Manhattan, KS, November 18, 2010
Keywords: http://www.aasv.org/shap.html; Swine; Creep feed; Growth; Feeder design; Suckling pig